A Replicable Capacity-Building Workshop to Raise Lecturers’ SINTA Scores by 1000 in One Year - Lilis Suryani; Hendra Halim; Abdurrahman; Arifin Ahmad; Ibrahim; Ichwansyah (Jurnal Pengabdian Bakti Akademisi, 2026)
This community service program aimed to strengthen lecturers’ capacity to improve SINTA performance by transforming community-service activities into publishable outputs. Using a service-learning (SL) approach integrated with a publication pipeline, the program was implemented through (1) needs assessment and baseline mapping, (2) a core workshop on manuscript structure, ethical publication, journal/publisher selection, and reference management, (3) writing clinics and peer-review in small groups, and (4) finalization and submission planning. The activities were conducted in one main session followed by a short mentoring follow-up period (2–4 weeks). Results indicated improved participants’ writing literacy and manuscript quality, with most participants producing complete drafts and a substantial proportion reaching “submission-ready” status. The program implies a replicable model to accelerate credible scholarly dissemination and support SDG 4, 9, and 17.